Biofuels in China: an analysis of the opportunities and challenges of Jatropha Curcas in Southwest China - Weyerhaeuser, Horst; Tennigkeit, Timm; Yufang S; Kahrl F (World Agroforestry Centre, 2007)
Over the past decade China has quietly emerged as the world’s third largest biofuel producer. Concerned over rising food prices, in June 2007 China’s central government banned the use of grain-based feedstocks for biofuel production and reoriented the country’s bioenergy plans toward perennial crops grown on marginal land. One such crop, Jatropha curcas, has emerged as a high potential biodiesel feedstock because of its adaptability to the diverse growing conditions where China’s marginal land is abundant. Provincial governments in Southwest China, for instance, have drafted ambitious plans to increase Jatropha by over one million hectares in the next decade. This paper analyzes the opportunities and challenges for the development of a Jatropha industry in Southwest China. Given the scarcity of data on Jatropha productivity and economics, we argue that plans to rapidly expand Jatropha acreage and refining capacity could jeopardize the industry’s longer-term viability. Alternatively, a commitment to silvicultural, engineering, and economic research could set the industry on a more sustainable path.